Immunology meets neuroscience - opportunities for immune intervention in neurodegenerative diseases - LYNCH, MARINA; MILLS, KINGSTON (My University, 2011)
Neuroinflammatory changes are characteristic of many, if not all, neurodegenerative diseases but the extent to which the immune system is involved in the pathogenesis of these diseases is unclear. The findings of several studies during the past decade has established that there is a well-developed communication between the central nervous system (CNS) and the peripheral immune system, but also has revealed that the immune system in the CNS is much more sophisticated that previously acknowledged. In this mini-review, we discuss two major neurodegenerative disorders, Alzheimer?s Disease (AD) and multiple sclerosis (MS), and consider whether the therapies most likely to succeed are those that are identified by studying the marriage of neuroscience and immunology.
PUBLISHED
Keywords: Immunology; Neuroscience; Immunology, Inflammation & Infection